Sustainability Accounting Compliance Under IFRS S2: Carbon Emission Disclosure in Public Enterprises Across Three Regulatory Phases, A Systematic Literature Review - Widyaningsih Azizah; Eka Sudarmaji (Journal of International Accounting, Taxation and Information Systems, 2026)
This review examines how public enterprises across three regulatory phases which are voluntary disclosure, mandatory adoption, and early enforcement comply with carbon emission disclosure requirements under IFRS S2 Climate-related Disclosures, issued by the International Sustainability Standards Board in June 2023. Despite the growing urgency of climate accountability, empirical evidence on whether public enterprises genuinely meet IFRS S2 obligations, and what explains variation in compliance quality, remains fragmented. A systematic search of four databases (Google Scholar, Semantic Scholar, Scopus, and CrossRef) produced a final corpus of 154 peer-reviewed articles, book chapters, and conference papers published between 2006 and 2026, screened according to PRISMA guidelines. Thematic synthesis identified three overlapping evidence clusters: standard adoption readiness in emerging economies, governance and board-level determinants of disclosure quality, and the role of digital data infrastructure in enabling compliance. Findings show that larger, state-affiliated enterprises in jurisdictions with pre-existing mandatory frameworks tend to disclose more completely, while most developing-country evidence points to moderate disclosure indices, persistent Scope 3 gaps, and significant institutional capacity deficits. The review supports three empirical hypotheses: compliance quality improves with regulatory phase progression, board governance quality positively moderates that relationship, and digital data capability independently predicts compliance quality across all three phases. Practically, the findings argue for sequenced implementation strategies that align regulatory mandates with investments in governance structures, carbon accounting capacity, and ESG data infrastructure. IFRS S2 compliance is not purely a technical reporting exercise; it is a function of institutional commitment, organisational governance, and digital readiness.